Triptorelin nanoparticle-loaded microneedles for use in assisted reproductive technology - Xiaoyan Lu; Yiying Sun; Meishan Han; Daoyuan Chen; Xiaoyan He; Siqi Wang; Kaoxiang Sun (Taylor & Francis Group, 2023)
AbstractTriptorelin is a first-line drug for assisted reproductive technology (ART), but the low bioavailability and frequent subcutaneous injection of triptorelin impair the quality of life of women preparing to become pregnant. We report silk fibroin (SF)-based microneedles (MNs) for transdermal delivery of triptorelin-loaded nanoparticles (NPs) to improve bioavailability and achieve safe and efficacious self-administration of triptorelin. Triptorelin was mixed into an aqueous solution of SF with shear force to prepare NPs to control the release and avoid the degradation of triptorelin by enzymes in the skin. Two-step pouring and centrifugation were employed to prepare nanoparticles-encapsulated polymeric microneedles (NPs-MNs). An increased β-sheet content in the conformation ensured that NPs-MNs had good mechanical properties to pierce the stratum corneum. Transdermal release of triptorelin from NPs-MNs was increased to ∼65%. The NPs-MNs exhibited a prolonged drug half-life and increased relative bioavailability after administration to rats. Surging levels of luteinizing hormone and estradiol in plasma and their subsequent prolonged downregulation indicate the potential therapeutic role of NPs-MNs in ART regimens. The triptorelin-loaded NPs-MNs developed in this study may reduce the physical and psychological burden of pregnant women using ART regimens.